Nafas Kesadaran dan Menghidupkan Spiritualitas Melalui Integrasi Tasawuf dan Psikologi - M Iqbal Irham (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
This article explains about an effort of livening up spirituality in one’s self based on religious understanding, namely through the doctrines and values of Sufism in order to get close to God (taqarrub ilâ Allâh). It aims to reach spiritual theistic using a method of “the Breath of Consciousness”. The method uses breath, i.e. inhaling and exhaling, as we usually do. The method consists of three important steps, are: breathing calmly, breathing deeply, and breathing gently. The key to the success of this method is consistent implementation (istiqa}mah) and simultaneous practice. “The Breath of Consciousness” should be done through seven sequential steps and stages, namely breathing in consciousness, looking in consciousness, feeling in consciousness, moving in consciousness, walking in consciousness, speaking in consciousness, and presence in consciousness. The expected contribution of the method is providing the society, especially the Muslim community, an easy technique to get close to God. Moreover, the method—when implemented correctly—will result in healthy body, pure mind, quiet soul, and peaceful heart. In doing so, the article aims to elaborate the integration of psychology and Sufism as an approach to the study of soul and consciousness.